Recent urban studies, Bangladesh : a collection of USP research papers - Islam, Nazrul, 1941-; University of Dhaka. Urban Studies Programme (Dhaka : Urban Studies Programme, Dept. of Geography and Environment, University of Dhaka, 1998)
Contributed papers.
Cover title.
Includes bibliographical references.
Keywords: Cities and towns -- Research -- Bangladesh; Urbanization -- Research -- Bangladesh; Urban policy -- Research -- Bangladesh